The Eritrean Islamic movement and its political role in Eritrea: case study of the Eritrean Islamic party for justice and development / Idris Abubeker Ibrahim - Idris, Abubeker Ibrahim (2016)

(untitled)
This study gives a brief background about the spread of Islam in the Abyssinian region in general and in Eritrea in particular, as well as it explores the role and contributions of the Eritrean Muslims in the Eritrean national movement struggle up to the independence day in 1993. The study discusses and analyses the history of the Eritrean Islamic movement in depth, starting from The initial influence which commenced during the 1950s and 1960s in which some well-known Eritrean figures were influenced by the Egyptian Muslim Brotherhood’s (MB) ideology, followed by formations of cells within the Eritrean society in the first half of the 1970s. The time of the Muslim pioneers organisation in the 1980s, The establishment of the Eritrean Islamic Jihad movement which sprang from the conference of unification of the Eritrean Islamist groups in November 1988 coupled with its political and organisational developments in the Eritrean arena. Equally, the study exposes the challenges and setbacks of the organisation. One of its obvious setbacks was the internal division in 1993 which led to two factions (Muslim brotherhood and Salafi group). Since then, the Islamist factions in Eritrea continued to gain ground but also faced obstacles. This study adopted historical and analytical methods in order to recognise the multidimensional nature of the issue. The study has been divided into six chapters, including the introductory and the conclusion chapters which contain the research findings and recommendations.